Traduceri şi traducători în scrisul beletristic din secolul al XVIII-lea - Gheorghe Chivu (Revista de Istorie și Teorie Literară)
During the 18th century, numerous Neo-Greek fiction texts, but also an increased number of texts of Italian, French or Spanish literatures were translated into Romanian by secular scholars, and often by clerics influenced by the Enlightenment. These translations, generally not part of a program, simply illustrating the intellectual disposition of the scholars of that time, renewed the Romanian fictional writing thematically and rhetorically, setting the stage for the profound changes that will appear in the first decades of the 19th century.